2016
DOI: 10.1038/srep25625
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evidence for the effects of multiple drivers on continental-scale amphibian declines

Abstract: Since amphibian declines were first proposed as a global phenomenon over a quarter century ago, the conservation community has made little progress in halting or reversing these trends. The early search for a “smoking gun” was replaced with the expectation that declines are caused by multiple drivers. While field observations and experiments have identified factors leading to increased local extinction risk, evidence for effects of these drivers is lacking at large spatial scales. Here, we use observations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(159 citation statements)
references
References 43 publications
5
152
1
1
Order By: Relevance
“…Given the concomitant large-scale loss and degradation of wetland habitats (Davis and Froend 1999, Gibbs 2001, Zedler and Kercher 2005, it is not surprising that habitat modification is the most implicated source of amphibian declines (reviewed in Alford and Richards 1999). However, a suite of other interrelated factors have also been linked to amphibian declines and vary depending on context, species, and region (Grant et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Given the concomitant large-scale loss and degradation of wetland habitats (Davis and Froend 1999, Gibbs 2001, Zedler and Kercher 2005, it is not surprising that habitat modification is the most implicated source of amphibian declines (reviewed in Alford and Richards 1999). However, a suite of other interrelated factors have also been linked to amphibian declines and vary depending on context, species, and region (Grant et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…They concluded that declines may be more widespread and severe here than previously recognized, but did not assign any specific cause to any of these declines. Grant et al [89] compared the spatial patterns and intensities of four threats-including chytridiomycosis-to declines in species occupancy for those US Geological Survey data and concluded that no single threat was consistent in explaining observed trends and that amphibian response to the threats varied spatially.…”
Section: (V) Eastern United Statesmentioning
confidence: 99%
“…Examples of regional ecological variation are not uncommon for amphibians. Recently, it was reported that local amphibian population declines across North America were not attributable to any single continental or regional‐scale stressor and that the effect of each stressor varied across regions (Grant et al ). Moreover, numerous studies have identified direct and indirect negative effects of fish on wood frogs (Egan and Paton , Eaton et al , Herwig et al , Carlson and Langkilde ), whereas others have concluded that fish do not significantly affect wood frog population metrics (Schank et al , Davenport et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly numerous ecological successes have resulted from extrapolating inferences across regions and ecological gradients; however, region‐specific research may identify unique threats and ecological relationships important to the focal species’ persistence within the respective region (Grant et al ). Consequently, the efficacy of conservation and management plans, which will undoubtedly continue to be informed by out‐of‐region research, may hinge on their capacity to effectively integrate novel information.…”
Section: Discussionmentioning
confidence: 99%